1994
DOI: 10.1093/nar/22.15.3226
|View full text |Cite
|
Sign up to set email alerts
|

Cyanine dye dUTP analogs for enzymatic labeling of DNA probes

Abstract: Fluorescence in situ hybridization (FISH) has become and indispensable tool in a variety of areas of research and clinical diagnostics. Many applications demand an approach for simultaneous detection of multiple target sequences that is rapid and simple, yet sensitive. In this work, we describe the synthesis of two new cyanine dye-labeled dUTP analogs, Cy3-dUTP and Cy5-dUTP. They are efficient substrates for DNA polymerases and can be incorporated into DNA probes by standard nick translation, random priming an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 36 publications
3
58
0
3
Order By: Relevance
“…The plasmids were amplified in E. coli and purified by phenol-chloroform extraction. Nick-translation was performed by the given procedure for the preparation of biotinylated 50-200-bp fragments (Yu et al 1994). DNAse (10 units/ l, Boehringer-Mannheim, Indianapolis, IN) was used to cut the plasmid into 100-200-bp fragments.…”
Section: Dna Probe and Labelingmentioning
confidence: 99%
“…The plasmids were amplified in E. coli and purified by phenol-chloroform extraction. Nick-translation was performed by the given procedure for the preparation of biotinylated 50-200-bp fragments (Yu et al 1994). DNAse (10 units/ l, Boehringer-Mannheim, Indianapolis, IN) was used to cut the plasmid into 100-200-bp fragments.…”
Section: Dna Probe and Labelingmentioning
confidence: 99%
“…These amino reactive dyes required for nucleic acid labeling are hydrophilic in nature which is advantageous for stabilization when conjugated to DNA [4]. Fluorescence-based nucleic acid hybridization assays are much important in various studies like gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of two new cyanine dye-labeled dUTP analogs, Cy3-dUTP and Cy5-dUTP has been reported [4]. They are efficient substrates for DNA polymerases and can be incorporated into DNA probes by standard nick translation, random priming and polymerase chain reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the emission maxima have to be well separated from each other to allow sufficient resolution of the signal. A typical multi color triplet of fluorophores would, for example, include Cy3, TRITC and Cy5 [49].…”
Section: Multicolor Labellingmentioning
confidence: 99%
“…The second way is to label each nucleic acid probe with a fluorophore with distinct spectral properties. Waggoner et al [49] reported on the synthesis of two new cyanine labelled dUTP analogs of Cy3 and Cy5 and demonstrated their use in a multicolor multisequence analysis approach based on in-situ hybridization techniques.…”
Section: Hybridization Assaysmentioning
confidence: 99%